PROPOSED PRODUCT PLACEMENT IN SHORT MOVIE AS PROMOTION CHANNEL FOR SMEs - SELLA MONIKA - Nim: 29116513 , GELDA
Academy of Motion Picture Arts and Sciences has defined short movie as an original motion picture that has a running time of 40 minutes or less, including all credits. Compared with feature films that have become very attractive for investors or businessmen, the commercial value of short movie is still considered negligible. However, the trend of short films is actually starting to rise again in recent years, when people can access the internet easily (Kolbenschlag, 2014). While the trend using movie as marketing tools is growing, it becomes the opportunity but also challenge for the short movie makers since it can be a way to get fund for their short movie. Most of big company choose to collaborate with good name or agency who have had portfolio and good reputation. Nevertheless, creators can still looking for opportunity in business players with lower level that are easier to reach and engage with, which is Small Medium Enterprises (SMEs). This is a good opportunity for movie creators to get funding for their project if they are able to convince SMEs. Hence, this research aims to know how SMEs can be attracted to use product placement (PPL) in short movies as their promotion tools by conducting both qualitative and quantitative method. Interviews with SMEs were conducted, and secondary data were collected to determine a set of criteria that affects SMEs' product placement's decisions which later be compared to each other by using Pairwise Comparison Method to find out the most important factors for the SMEs who are willing to use product placement in short movie as their promotion channel. The data were calculated through ExpertChoice. The results show 10 list of the most important factors that affects SMEs’ willingness to use product placement in short movie as their promotion channels. They are target audience (17%), interaction of audience (16%), PPL strategy (14%), Story (13%), distribution channels (10%), duration (7%), price range (6%), influencer/popular name (6%), PH’s reputation (6%), and Other brands promoted (5%). However, the researcher recommend that the short movie makers should at least focus on the most important factors which are short movie target audience, interaction of audiences, PPL strategy, and story to get 60% possibility that SMEs will be attracted to buy product placement in our short movie as their promotional channel. However, it is also found that the most important factors for different product category are also different. The product who has specific target or characteristic such as fashion, accesorries, make up & skin care are chosen target audiences as the most important thing. For the F&B (in package) product, the most important factor is the interaction of audiences where short movie can get many response, comment, or reviews, especially for the appearance of their product. And for the complementary product such as stationary and place/space they choose product placement strategy as the most important factors. At the end, the list of most important factors and other supporting findings are used to give recommendation for creators on how to offers product placement in their short movie project to SMEs.